2022
DOI: 10.3390/educsci12020146
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Equity and Assuring Teaching and Learning Quality: Magisterial Lectures in a Philippine University during the COVID-19 Pandemic

Abstract: When the COVID-19 pandemic forced universities to shift to online learning, one of the challenges to faculty and administrators was to provide students with high-quality, curriculum-based learning materials that could be accessed despite students’ variable levels of Internet access. Part of the Ateneo de Manila University’s response to this challenge is the production of the Magisterial Lectures, an Open Educational Resource (OER) series of video lectures by some of the University’s most respected faculty memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In [27], the authors discussed the use of YouTube analytics both to assess student attendance during lectures and to measure the impact of lectures on the student learning experience. Going further, the authors in [28] planned campaigns by processing analytics data from the tools offered by social media channels.…”
Section: Related Workmentioning
confidence: 99%
“…In [27], the authors discussed the use of YouTube analytics both to assess student attendance during lectures and to measure the impact of lectures on the student learning experience. Going further, the authors in [28] planned campaigns by processing analytics data from the tools offered by social media channels.…”
Section: Related Workmentioning
confidence: 99%
“…They found that these respondents were more likely to self-identify as members of an economically disadvantaged group. To promote equity and to ensure the quality of teaching and learning during the pandemic, Rodrigo et al [3] produced OERs in the form of video lectures and made the resources available online at no cost. Their OERs benefited students regardless of their socioeconomic status and reached over 350,000 viewers across 37 countries in around one year and a half.…”
Section: Benefits Of Using Oersmentioning
confidence: 99%
“…These findings might indicate the need to create more quality OERs that are easy to find. Some teachers reported that locating video lectures on YouTube was easier than searching on their university OERs websites [3], suggesting that methods of retrieving OERs from repositories need to improve.…”
Section: Challenges To the Use Of Oersmentioning
confidence: 99%
See 1 more Smart Citation
“…Students have problems participating (Anthonysamy, 2022), which lowers the focus (Giray et al, 2022), rejected virtual lessons (Rodrigo & Ladrido, 2022), and actively participated in dialogues (Tiria et al, 2022). COVID-19 requires instructors, in order to develop techniques to maximise learning (Neuwirth et al, 2021).…”
Section: Challenges To Virtual Learningmentioning
confidence: 99%